Analysis of grid-connected solar PV system integrated with battery energy storage for Hospital Putrajaya - Shairam Salleh (2020)
The number of solar photovoltaics (PV) system installation is rising globally. This generates increased competition, with new players entering the market. In turn, this necessitates the need to ensure new technology to respect adequate safety, quality and performance requirements. The biggest challenge in the government hospitals is the high building operational cost. This is because hospitals are equipped with equipment and system that are high in kilowatt demand. In this regard, air conditioning system has the highest operation cost. To address this, the solar PV system integrated with battery energy storage (BES) has been proposed in this work. It could shave the system’s maximum demand (MD), which could reduce the electricity bill for the hospital. Therefore, the design of solar PV system integrated with battery energy storage has been carried out with technical and economic analysis. The study takes into the consideration of the voltage profile in order to avoid voltage rise problem in the Hospital Putrajaya’s distribution system. This project is expected to shave the MD of the hospital and provide the energy and money saving to the Hospital Putrajaya.